The Problems with the Critique of Political Economy in the Arts - Mi You (Lateral)
This article attempts to offer a systemic discussion about the paradigm shift away from the neoliberal Washington consensus and its ramifications for the worlds of performing and visual arts. The article first provides an overview of discussions of political economy in the arts, in which the typically speculative arguments are contrasted with sociological and historical knowledge which reveals a limit to them. The article then describes contemporary political economy in the era of post-globalization and makes a few proposals on how the arts can think through it.